MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DALAM MENINGKATKAN PROFESIONALISME GURU DI SMP IT DARUSSALAM SRAGEN - Etik Kurniawati (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2019)
AbstracTo improve teacher competency in schools one way is through the management of Islamic education institutions that favor the improvement of teachercompetencies. What is the supervision of Islamic education institutions inincreasing the professionalism of teachers in the Darusalam Middle School Sragen.This study aims to describe the management plan of Islamic education institutionsin enhancing the professionalism of teachers at the Darusalam Middle School inSragen.. The research subjects were the Principal of the Middle School ofDarussalam Darussalam Sragen, Deputy Head of Affairs (curriculum, studentaffairs, finance, facilities), TU Staff and Teachers. Data obtained throughobservation, interviews, and documentation. After collecting data, presenting data,and analyzing data. The data shows that the increase in the competence of teachersat the IT Darussalam Middle School can be achieved through two things, namelythe efforts of teachers and the participation of educational institutions. The effortsof teachers in order to improve their competence through four things, include:pedagogical, personal, social and professional competencies.Key Word: Management of Islamic Education Institutions, Teacher ProfessionalismAbstrakMeningkatkan kompetensi guru di sekolah salah satu caranya adalah melalui manajemen lembaga pendidikan Islam yang berpihak pada peningkatankompetensi guru. Penelitian ini bertujuan Mendeskripsikan perencanaan manajemenlembaga pendidikan Islam dalam meningkatkan profesionalisme guru di SMP ITDarusalam Sragen. Subjek penelitian adalah Kepala Sekolah SMP IT DarussalamSragen, Wakil Kepala urusan (kurikulum, kesiswaan, keuangan, sarana prasarana),Staf TU dan Guru. Data diperoleh melalui observasi, wawancara, dan dokumentasi.Setelah melakukan pengumpulan data, penyajian data, dan analisis data diperolehdata bahwa peningkatan kompetensi guru SMP IT Darussalam dapat diraih melaluidua hal yaitu dengan usaha dari guru dan peran serta lembaga pendidikan. Upayaguru dalam rangka meningkatkan kompetensinya melalui empat hal, meliputi:kompetensi pedagogik, pribadi, sosial dan profesional. Kata Kunci: Manajemen Lembaga Pendidikan Islam, Profesionalisme Guru